Pharmacokinetics and toxicology of a fibroblast activation protein (FAP)‐activated prodrug in murine xenograft models of human cancer. Issue 13 (22nd July 2014) - Brennen, W. Nathaniel; Rosen, D. Marc; Chaux, Alcides; Netto, George J.; Isaacs, John T.; Denmeade, Samuel R.
<x xml:space="preserve">Abstract</x> BACKGROUND As carcinoma progresses, the stroma undergoes a variety of phenotypic changes, including the presence of carcinoma‐associated fibroblasts (CAFs) that express fibroblast activation protein (FAP). FAP is a post‐prolyl endopeptidase whose expression in a healthy adult is largely restricted to the cancer‐associated stroma. FAP‐targeted prodrugs with a 100‐fold greater therapeutic window over the parent compound were previously generated. METHODS Prodrugs and non‐cleavable controls were incubated in the presence of FAP. Plasma and tumor half‐lives (t1/2) of the full‐length and active forms of the prodrugs were determined using LCMS. Biodistribution studies of prodrug activation were performed. Histopathological analysis of tissues from treated animals were compared to vehicle‐treated controls. Toxicity and efficacy studies were performed in human breast (MDA‐MB‐231 and MCF‐7) and prostate (LNCaP) cancer xenografts models. RESULTS These FAP‐activated prodrugs have a significantly slower clearance from tumor tissue than the circulation (∼12 vs. ∼4.5 hr). Micromolar concentrations of active drug persist in the tumor. Active drug is detected in non‐target tissues; however, histopathologic evaluation reveals no evidence of drug‐induced toxicity. A FAP‐activated prodrug (ERGETGP‐S12ADT) inhibits tumor growth in multiple human breast and prostate cancer xenograft models. The anti‐tumor effect is comparable to that observed with docetaxel, but results in significantly less toxicity. CONCLUSION FAP‐activated prodrugs are a viable strategy for the management of prostate and other cancers. These prodrugs exhibit less toxicity than a commonly used chemotherapeutic agent. Further refinement of the FAP cleavage site for greater specificity may reduce prodrug activation in non‐target tissues and enhance clinical benefit. Prostate 74: 1308–1319, 2014. © 2014 Wiley Periodicals, Inc.